Effectiveness of Next Generation Regional Management Information System Implementation at the Regional Finance and Asset Agency of North Sulawesi Province - Goinpeace H. Tumbel; Devie S. R. Siwij; Virginia T. Tiranda (Technium Social Sciences Journal, 2023)
This study aim to determine the effectiviness of the implementation of the Next Generation Regional Management Information System in North Sulawesi Province Regional Financial and Asset Management. The approach used in this study is a qualitative descriptive approach. The results showed that implementation of SIMDA NEXT-G was seen from 1) the program success indicators were quite effective, because they were in accordance with the main objectives and functions, namely being able to produce the right information for local governments so that the information produced could be useful in making decisions and helping employees or staff ini facilitating financial management and being able to store financial data for future management purposes, 2) target success is declared not effective enough because there are problems with the SIMDA NEXT-G server which often has errors because the server is based at BPKP, 3) satisfaction with the program is stated not quited effective bevause there are still several menus dan features that are not yet available ini implementation and administration, 4) Achievment of overall objectives is not effective enough because the level of timeliness of SIMDA NEXT-G depends on the situation and conditions at that timen. If, on that day the server is down and there is interference. The SIMDA NEXT-G cannot be accessed which hinders work.